Oral mucosal lesions: findings from the Australian National Survey of Adult Oral Health. (4th February 2014) - Do, LG; Spencer, AJ; Dost, F; Farah, CS
Abstract Background The prevalence of oral mucosal lesions (OMLs) and factors associated with these has not previously been reported in the Australian population. This study aimed to report on the prevalence of OMLs in Australian adults and to evaluate their association with socio‐demographic factors. Methods This study utilized data from the Australian National Survey of Adult Oral Health 2004–06, which employs a multi‐stage, stratified random sample selection procedure. Information on socio‐demographics, smoking and presence of OMLs were collected using telephone interview, self‐reported questionnaires and comprehensive oral examination. A multivariate regression model was generated to estimate effect of factors on the prevalence of non‐ulcerated OMLs. Results A total of 3551 dentate adult Australians had complete data for this analysis. Over 20% of study participants presented with an OML on the day of examination. The prevalence of suspected malignancy was less than 1% and over 17% for non‐ulcerated OMLs. Prevalence of non‐ulcerated OMLs was associated with age, gender, residential location, household income and smoking. Conclusions The study reported that epidemiological survey can provide useful information on OMLs. Certain population groups had a higher risk of having the condition. Preventing smoking uptake and smoking cessation can reduce the prevalence of OMLs in the population.